Advantages and disadvantages of desflurane versus sevoflurane - Van Speybroeck, Phaedra; Mulier, Jan Paul; De Baerdemaeker, Luc (Best practice & research. Clinical anaesthesiology, 2024)
Increasing awareness of environmental sustainability in healthcare has prompted scrutiny of inhaled anesthetics, especially concerning their contributions to greenhouse gas emissions. Among these agents, desflurane and sevoflurane have been the subject of extensive debate, not only regarding their environmental impact but also their clinical performance. An overview of the utility of desflurane and sevoflurane in different patient populations is given, which yields a minor advantage in awakening times for desflurane in obese patients and children. However, desflurane’s side effects may outweigh its benefits in routine practice. As a conclusion, the decision to use desflurane or sevoflurane should be patient-orientated, with considerations of environmental sustainability and future research focused on improving anesthetics techniques.